Bagay gabay sa pagsulat sa wikang Filipino - Yapan, Alvin B. (Quezon City BlueBooks, Ateneo de Manila University Press, 2017)
Guidelines on writing Filipino grammar.
Includes bibliographical references (pages x-xi) and index.
Keywords: Tagalog language -- Grammar -- Handbooks, manuals, etc; Tagalog language -- Writing -- Handbooks, manuals, etc